The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2310/jim.0b013e3182857edf
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Impaired Global Right Ventricular Function in Patients with a Reperfused Acute Myocardial Infarction and without Right Ventricular Infarction

Abstract: In patients with a first acute STEMI without an associated RV infarction, depressed global LV function reflected by increased TDI-derived LV MPI, a lower mitral E/A ratio, and a higher glucose level on admission are independent correlates of early global RV dysfunction. Routine assessment of global RV function should be implemented in patients with STEMI with these characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 34 publications
6
8
4
Order By: Relevance
“…The superiority of RVFAC over most other classical echocardiographic parameters could be due to its ability to take into account both longitudinal and radial shortening [15]. Local longitudinal parameters such as TAPSE and S 0 velocity failed to show any significant differences related to the location of MI at the acute phase in our patients with relatively preserved RV function [16]. This is in accordance with other studies reporting a poor diagnostic power of conventional parameters for initial RV extension of MI [17].…”
Section: Screening Of Rv Dysfunction After Stemisupporting
confidence: 89%
“…The superiority of RVFAC over most other classical echocardiographic parameters could be due to its ability to take into account both longitudinal and radial shortening [15]. Local longitudinal parameters such as TAPSE and S 0 velocity failed to show any significant differences related to the location of MI at the acute phase in our patients with relatively preserved RV function [16]. This is in accordance with other studies reporting a poor diagnostic power of conventional parameters for initial RV extension of MI [17].…”
Section: Screening Of Rv Dysfunction After Stemisupporting
confidence: 89%
“…The lower incidence of RV involvement in the studies by Hsu et al [4] and Karakurt and Akdemir [12] than in our study could be explained by higher risk profile of our patients such as diabetes mellitus (DM; 87.5%) in our study, 28.5% in Hsu et al study [4], and 25.9% in Karakurt and Akdemir study [12], which may affect the microvascular integrity leading to higher incidence of RV involvement.…”
Section: Discussioncontrasting
confidence: 56%
“…Hsu et al [4] studied a total of 102 consecutive patients admitted with the first episode of acute MI and found that 17% of the study population who presented with anterior STEMI and underwent primary PCI had RV dysfunction, yet inferior wall MI was correlated with more impairment of RV function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equipment used was a Philip SONOS 7500 (Agilent Technologies, Andover, MA) system. All measurements were performed and repeated by the same experienced echocardiologist 16 , 17 . The LV end-diastolic volume index (LVEDVI) was measured according to the recommendations of the American Society of Echocardiography 18 .…”
Section: Methodsmentioning
confidence: 99%